Optical tomography: Image improvement using mixed projection of parallel and fan beam modes - Mohd Muji, Siti Zarina; Abdul Rahim, Ruzairi; Rahiman, Mohd Haﬁz Fazalul; Tukiran, Zarina; Nor Ayob, Nor Muzakkir; Mohamad, Elmy Johana; Puspanathan, Jaysuman (Elsevier Science Ltd, 2013)
Mixed parallel and fan beam projection is a technique used to increase the quality images. This research focuses on enhancing the image quality in optical tomography. Image quality can be deﬁned by measuring the Peak Signal to Noise Ratio (PSNR) and Normalized Mean Square Error (NMSE) parameters. The ﬁndings of this research prove that by combining parallel and fan beam projection, the image quality can be increased by more than 10%in terms of its PSNR value and more than 100% in terms of its NMSE value compared to a single parallel beam.